Introductory Remarks on the Essays of the Speakers of the XVIIth Young Scientists Meeting on Roman Law - Radek Černoch (Journal on European History of Law)
On April 13th and 14th 2023 Masaryk University in Brno (Czech Republic) hosted the XVIIth Young Scientists Meeting on Roman Law. The following introduction sums up topics and presentations of the Meeting. After the introductory remarks four speakers present their essays, based on their presentations at the Meeting.